Upaya Pemerintah Daerah Dan Masyarakat Mandar Dalam Melindungi Minyak Kelapa Mandar Dalam Persfektif Indikasi Geografis - Erlika Sari; Fediyatun Muntazarah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research examines the efforts of the local government and Mandar community in protecting Mandar coconut oil through a Geographical Indication (IG) perspective. Mandar coconut oil is one of the region's superior products with great potential to obtain GI protection due to its unique qualities and characteristics. However, until now, Mandar coconut oil has not been registered as an IG product. This research uses an empirical legal approach with interview and questionnaire methods to collect data from coconut oil producers in Majene and Polewali Mandar Regencies. The research results show that the protection of Mandar coconut oil is still not optimal. The main inhibiting factors are the lack of knowledge of the community and local government regarding intellectual property rights, lack of funding, and limited support from the government. Therefore, collaboration is needed between the government, community and other stakeholders to increase understanding and awareness of the importance of GI, in order to support the competitiveness of local products in the global market and protect the sustainability of Mandar coconut oil production.